Pirates of the Caribbean. Dead man's chest [videorecording (DVD)] - Verbinski, Gore; Depp, Johnny; Bloom, Orlando, 1977-; Knightley, Keira, 1985- (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Captain Jack owes a blood debt to the legendary Davy Jones, who captains the ghostly Flying Dutchman. Unless Jack can find a way out, he will be cursed to an afterlife of eternal servitude and damnation.